Digitalization Of Local Regulations: Challenges And Opportunities In Improving Legal Transparency And Accessibility In The Digital Era - Fuji SM Bako (ISNU Sumatera Utara, 2026)
The digitalization of Regional Regulations (Peraturan Daerah/PERDA) has become a strategic instrument in strengthening the implementation of electronic-based government (e-Government) and promoting the principles of good governance, particularly transparency, accountability, efficiency, and public participation. As regional governments produce an increasing number of legal instruments, the availability of an accessible, integrated, and reliable digital legal information system is essential to ensure legal certainty and improve public access to regional legislation. Nevertheless, the implementation of PERDA digitalization in Indonesia continues to face various structural, technological, and institutional challenges that hinder its optimal realization. This study aims to analyze the urgency of digitalizing Regional Regulations, identify the challenges encountered in its implementation, and examine the opportunities for strengthening an integrated digital legal governance system in Indonesia. The research employs a normative juridical method using a statutory, conceptual, and library research approach by examining legislation, legal doctrines, scholarly literature, and relevant policy documents concerning electronic governance and legal information systems. The findings indicate that the digitalization of Regional Regulations, particularly through the Legal Documentation and Information Network (JDIH), has significantly improved public accessibility to regional legal products, enhanced transparency in legislative processes, and facilitated legal harmonization and administrative efficiency. However, its implementation remains constrained by disparities in digital infrastructure among regions, the absence of standardized digital governance mechanisms, limited interoperability between information systems, budgetary constraints, and inadequate digital literacy and technical capacity of government personnel. The study concludes that optimizing the digitalization of Regional Regulations requires the establishment of a nationally standardized and interoperable digital legal information system, supported by sustainable infrastructure development, institutional capacity building, and comprehensive regulatory harmonization to realize effective, transparent, and inclusive digital governance.